2007
DOI: 10.1007/s10597-007-9084-9
|View full text |Cite
|
Sign up to set email alerts
|

The Stigma of Psychiatric Disorders and the Gender, Ethnicity, and Education of the Perceiver

Abstract: The purpose of this study is to determine how the demographics of perceivers influence their stigma of people with mental illness or with substance abuse. A nationally representative sample (N = 968) was asked to respond to a vignette describing a person with a health condition (schizophrenia, drug dependence, or emphysema) and his/her family member. Consistent with our hypotheses, women were less likely to endorse stigma than men. Participants with higher education were also less likely to stigmatize than les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
196
2
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(242 citation statements)
references
References 48 publications
25
196
2
9
Order By: Relevance
“…Researchers have identified mental health stigma across multiple communities, and have demonstrated a clear link between stigma and mental health (Abdullah & Brown, 2010;Corrigan, 2004;Corrigan & Watson, 2007;Kira et al, 2014a). Although mental health stigma is common, the factors that maintain it and how it affects the individual differ by culture and community.…”
Section: Mental Health Stigma and Mental Healthmentioning
confidence: 99%
“…Researchers have identified mental health stigma across multiple communities, and have demonstrated a clear link between stigma and mental health (Abdullah & Brown, 2010;Corrigan, 2004;Corrigan & Watson, 2007;Kira et al, 2014a). Although mental health stigma is common, the factors that maintain it and how it affects the individual differ by culture and community.…”
Section: Mental Health Stigma and Mental Healthmentioning
confidence: 99%
“…18,19 It is relevant to note that psychiatric disorders are among the most profoundly stigmatized of all health conditions, and negative attitudes toward these conditions have been identified in many groups including the general public, [20][21][22][23] students, 24 police, 25 mental health workers, 26,27 and genetic counselors. 28,29 Medical geneticists' attitudes toward individuals with psychiatric disorders, and the relationships between these attitudes and clinical practice regarding disclosure of information about psychiatric risks, have not been previously studied.…”
mentioning
confidence: 99%
“…Among a sample of college students, African Americans endorsed lower benevolence and higher authoritarianism and social restrictiveness compared to Caucasians, while Hispanic students had similar ratings to Caucasians of benevolence and social restrictiveness (de Crane and Spielberger 1981). Corrigan and Watson (2007) also found that compared to Caucasians, ethnic minority participants endorsed higher levels of stigma toward individuals with mental illness and their families. Despite the fact that these studies highlight the interwoven nature of culture in mental health beliefs and attitudes, existing measures largely assess stigma as an etic construct and are not sensitive to capturing culturally nuanced stigma beliefs.…”
Section: Perceived Norms Of External Responses To Individuals With Mementioning
confidence: 81%